Population biology of the freshwater anomuran Aegla longirostri (Aeglidae) from South Brazilian streams - Colpo, K. D.; Ribeiro, L. O.; Santos, S. (Crustacean Soc, 2005)
This paper describes a population of Aegla longirostri from Ibicui-Mirim River, Itaara, Rio Grande do Sul State, Brazil, evaluating the size at onset of sexual maturity, relative growth, mean size, size-frequency distribution, sex ratio, ovigerous-rate, and recruitment. Samples were collected monthly from September 1996 to August 1997. Sex, carapace length (CL), cheliped length (ChL), abdomen width (AW), and front width (FW) were recorded for each crab. A total of 586 specimens were collected (277 males, 244 females, and 65 unsexed juveniles). The smallest specimen was 1.5 mm CL and the largest male was 23.8 mm CL. The relative growth analysis and the Mature software showed that the size at onset of sexual maturity was 13.7 mm CL in males and 10.7 mm CL in females. Females were smaller than males and were more abundant in adult classes, whereas males were more representative in juvenile classes. The sex ratio did not differ from 1:1 throughout the collecting period. Recruitment was observed throughout the entire sampling period, but it was higher in the winter months (from June to August). However, ovigerous females were present in spring and summer (from January to April). This population seemed to be at equilibrium during the study period. Recently, this area has been changed because of the construction of a reservoir, and a new study is required to evaluate the present condition of this population of A. longirostri.